Effect of trapping methods on the estimation of alpha diversity of a phlebotomine sandfly assemblage in southern Mexico - Rodríguez Rojas, Jorge Jesús; Rebollar Téllez, Eduardo Alfonso (Royal Entomological Society of London, 2017)
The aims of the study were to (a) investigate the effect of trapping methods on alpha diversity; and (b) enhance the knowledge of the sandfly assemblage in the state of Quintana Roo. Field work was undertaken in a tropical forest of southern Mexico from August 2013 to July 2014. Sampling was conducted monthly during three consecutive nights. For each trapping night, 12 different types of trap were operated from 18.00 to 24.00 hours in four transects. Measures of alpha community diversity were based on the quantification of the number of species (Chao 2, Jackknife 2, Clench’s equation, Margalef’s index) and the community structure, as well as the dominance (Simpson and Berger-Parker indexes) and evenness (Shannon’s entropy index, true diversity of the Jost and Pielou index). With a total sampling effort of 1728 night-traps, 16 101 phlebotomine sandflies were collected; they represented two genera and 13 species. Diversity estimatesof 100% (Chao 2 and Clench’s equation) and 85% (Jackknife 2) of potential species in the study area were calculated. Shannon traps and CDC light traps indicated the largest number of species, but only Shannon traps showed the greatest abundance. This inventory of sandflies is an important activity to enhance our knowledge of sandfly assemblages and guilds. The ultimate goal of studying alpha diversity in sandflies would be to have a better understanding of the population dynamics and all complex networks of interactions that may, in turn, be associated with the epidemiology of the disease.